Prognostic significance of right ventricle to pulmonary artery coupling in patients with mitral regurgitation treated with the MitraClip system. Issue 4 (23rd December 2021) - Popolo Rubbio, Antonio; Testa, Luca; Granata, Giuseppina; Salvatore, Tanya; De Marco, Federico; Casenghi, Matteo; Guerrini, Marco; Oliva, Omar A.; Stefanini, Elisa; Barletta, Marta; Sisinni, Antonio; Poletti, Enrico; et al.
Abstract: Objectives: To evaluate the prognostic impact of baseline tricuspid annular plane systolic excursion/pulmonary artery systolic pressure (TAPSE/PASP) ratio, as an expression of the right ventricle–pulmonary artery (RV–PA) coupling, in patients with mitral regurgitation (MR) treated with the MitraClip. Background: Impaired RV to PA coupling is considered a marker of RV dysfunction. Methods: From February 2016 to February 2020, a total of 165 patients were evaluated and stratified in two groups according to a prespecified value of TAPSE/PASP ratio ≤ 0.36. Results: The median patients' age was 79 (men: 62.4%). Sixty‐three patients (38.1%) presented TAPSE/PASP ≤ 0.36 and were then compared with patients with TAPSE/PASP > 0.36. Functional MR etiology was more frequent in TAPSE/PASP ≤ 0.36 (71.4%; p = 0.046). Acute technical success was achieved in 92.7% of the population, without any significant difference between the two groups of study and with sustained results at 30‐day (device success: 85.5%; procedural success: 84.8%). On multivariate Cox regression analysis, after correction for body mass index, chronic kidney disease and left ventricle ejection fraction ≥30% but <50%, TAPSE/PASP ≤ 0.36 remained a sustained predictor of mortality and hospitalization for heart failure at one year after MitraClip (hazard ratio: 3.87; 95% confidence interval: 1.83–8.22; p ≤ 0.001). Kaplan–Meier all‐cause mortality and heart failure hospitalization rates at one year were consequently higher in patients with TAPSE/PASP ≤ 0.36 (39.4% vs. 14.8%; log‐rank p ≤ 0.001). Conclusion: Baseline TAPSE/PASP ratio seems independently associated with all‐cause mortality and heart failure hospitalization after MitraClip both in functional and degenerative MR.